THE BEAUTY OF SYMMETRY: UNDERSTANDING GROUP THEORY - Vikas Farooq (PT. Radja Intercontinental Publishing, 2023)
Symmetry is a fundamental aspect of nature, art, and science. It appears in various forms, from the symmetric patterns of a snowflake to the balanced compositions of classical music. Group theory, a branch of abstract algebra, provides a mathematical framework to understand symmetry. This paper explores the beauty of symmetry through the lens of group theory, elucidating its principles, applications, and significance in different fields such as physics, chemistry, and the arts. By delving into the historical development and key concepts of group theory, this research aims to illuminate the profound connections between mathematics and the inherent order in the world around us.